Costs of epilepsy and cost‐driving factors in children, adolescents, and their caregivers in Germany. (3rd August 2015) - Riechmann, Janna; Strzelczyk, Adam; Reese, Jens P.; Boor, Rainer; Stephani, Ulrich; Langner, Cornelia; Neubauer, Bernd A.; Oberman, Bettina; Philippi, Heike; Rochel, Michael; Seeger, Jürgen; Seipelt, Peter; et al.
Summary Objective To provide first data on the cost of epilepsy and cost‐driving factors in children, adolescents, and their caregivers in Germany. Methods A population‐based, cross‐sectional sample of consecutive children and adolescents with epilepsy was evaluated in the states of Hessen and Schleswig‐Holstein (total of 8.796 million inhabitants) in all health care sectors in 2011. Data on socioeconomic status, course of epilepsy, and direct and indirect costs were recorded using patient questionnaires. Results We collected data from 489 children and adolescents (mean age ± SD 10.4 ± 4.2 years, range 0.5–17.8 years; 264 [54.0%] male) who were treated by neuropediatricians (n = 253; 51.7%), at centers for social pediatrics ("Sozialpaediatrische Zentren, " n = 110, 22.5%) and epilepsy centers (n = 126; 25.8%). Total direct costs summed up to €1, 619 ± €4, 375 per participant and 3‐month period. Direct medical costs were due mainly to hospitalization (47.8%, €774 ± €3, 595 per 3 months), anticonvulsants (13.2%, €213 ± €363), and ancillary treatment (9.1%, €147 ± €344). The total indirect costs amounted to €1, 231 ± €2, 830 in mothers and to €83 ± €593 in fathers; 17.4% (n = 85) of mothers and 0.6% (n = 3) of fathers reduced their working hours or quit work because of their child's epilepsy. Independent cost‐driving factors were younger age, symptomatic cause, and polytherapy with anticonvulsants. Older age, active epilepsy, symptomatic cause, and polytherapy were independent predictors of higher antiepileptic drug (AED) costs, whereas younger age, longer epilepsy duration, symptomatic cause, disability, and parental depression were independent predictors for higher indirect costs. Significance Treatment of children and adolescents with epilepsy is associated with high direct costs due to frequent inpatient admissions and high indirect costs due to productivity losses in mothers. Direct costs are age‐dependent and higher in patients with symptomatic epilepsy and polytherapy. Indirect costs are higher in the presence of a child's disability and parental depression.